2008
DOI: 10.1007/s00134-008-1021-z
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory variations in aortic blood flow predict fluid responsiveness in ventilated children

Abstract: While respiratory variations in aortic blood flow velocity measured by pulsed Doppler before VE accurately predict the effects of VE, DeltaPS and DeltaPP are of little value in ventilated children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
3
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 26 publications
1
101
3
4
Order By: Relevance
“…We may not have evaluated stoke volume variability accurately, as PRAM has been found to be an inaccurate measure of SVI [24]. This may explain the discrepancy between our findings and the good prediction (AUROC 0.85) for aortic peak velocity, a variable closely related to stroke volume variability [45]. However, there is no reason to believe a similar error is present with PPV or SPV, as these were calculated directly from the arterial line.…”
Section: Study Limitationscontrasting
confidence: 54%
“…We may not have evaluated stoke volume variability accurately, as PRAM has been found to be an inaccurate measure of SVI [24]. This may explain the discrepancy between our findings and the good prediction (AUROC 0.85) for aortic peak velocity, a variable closely related to stroke volume variability [45]. However, there is no reason to believe a similar error is present with PPV or SPV, as these were calculated directly from the arterial line.…”
Section: Study Limitationscontrasting
confidence: 54%
“…Both pressure related and flow related surrogates of stroke volume variation have been studied. Two studies have found that DPP does not predict VR in patients in the PICU [8] and in the OR [10]. The same studies did find, and have been supported by two further studies [11,29], that aortic flow variation (DVpeak) is useful to predict VR in children.…”
Section: Discussionmentioning
confidence: 58%
“…Dynamic preload indicators, such as arterial pulse pressure variation (DPP), are variables that quantify the effects of mechanical ventilation on cardiac stroke volume, and have been shown in adults to predict VR [5][6][7]. Pediatric studies examining dynamic preload indicators [8][9][10][11] have found that respiratory variations in aortic blood flow predict VR in children.…”
Section: Introductionmentioning
confidence: 98%
“…Studies in infants and neonates have shown that fluid responders did not have an associated rise in blood pressure. 65,[69][70][71][72] Monitors of end organ perfusion have been used to titrate fluid therapy. Near infrared spectroscopy (NIRS) has shown that a systolic blood pressure fall of 37% from baseline is associated with significant cerebral desaturation.…”
Section: Dynamic Parameters -Any Use In Neonates?mentioning
confidence: 99%